2017
DOI: 10.1016/j.jcot.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient orthopaedic hardware removal in children: A cross-Sectional study

Abstract: While most commonly performed as an outpatient procedure, inpatient hardware removal occurs with relative frequency and is most often performed for infection, mechanical failure, or pain. Risk factors for infection-related removal were identified and provide a basis for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…There are very few studies that have assessed the cost of implant removal outside the setting of infection. 5 , 34 A pediatric database study found that the cost of inpatient implant removal to be on average $11,792. 34 However, this included implant removals for infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are very few studies that have assessed the cost of implant removal outside the setting of infection. 5 , 34 A pediatric database study found that the cost of inpatient implant removal to be on average $11,792. 34 However, this included implant removals for infections.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 34 A pediatric database study found that the cost of inpatient implant removal to be on average $11,792. 34 However, this included implant removals for infections. A recent study reviewed the cost of implant removal for ankle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Vopat et al [ 63 ] showed that leaving the plates in pediatric forearm fractures does not increase the refracture rate compared with the plate removal. Indications for metallic material removal include pain, infection or soft tissue irritation [ 64 ].…”
Section: Platingmentioning
confidence: 99%
“…A refracture can occur after nonoperative and operative treatment, and there is a variable risk period after the removal of hardware of approximately 6 to 12 weeks. 3 It is unusual for these to occur a year later, and the ones reported 7,12 may have been caused by an occult lack of union or simply recurrence from overuse.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown even higher (7/12 patients; 58.3%) hardware removal rates for prominence and irritation after screw and washer fixation for medial epicondyle fractures but none for removal of a screw alone, highlighting the importance of the type of hardware used. 14 Boulos et al 3 examined pediatric hardware removal after fracture fixation in 2536 patients and found that infections (32%), mechanical failure (25.4%), and pain (13%) were the most common indications.…”
Section: Discussionmentioning
confidence: 99%